The Analysis Study of Association of Peripartum Cardiomyopathy and History of Tuberculosis : A Comprehensive Systematic Review - Putri, Syifa Nabila; Pangestu, Hedaya Pancar (International Medical Journal Corp. Ltd, 2024)
Background: Peripartum cardiomyopathy (PPCM) is a rare and potentially life-threatening condition affecting 1 in 1300 to 1 in 5,000 births, particularly in underdeveloped countries. It is characterized by difficulty breathing, lightheadedness, and fatigue. PPCM is more common in women with pre-eclampsia, chronic hypertension, smoking, alcohol abuse, advanced maternal age, malnutrition, long-term tocolysis, or a history of tuberculosis. Untreated PPCM increases the risk of complications like cardiogenic shock, arrhythmias, heart failure, cardiopulmonary arrest, and mortality. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2007 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. A number of websites, including ScienceDirect, PubMed, and SagePub, were utilized to gather the literature. Result: The study looked at more than 1800 publications using reputable sources including Science Direct, SagePub, and PubMed. After it was decided that eight publications needed greater investigation, a more extensive review of the entire literature was carried out. Conclusion: Pregnancy can lead to the development of Peripartum cardiomyopathy, a potentially fatal disorder, often diagnosed after delivery due to symptoms mimicking normal physiological findings. Tuberculosis, a common cause of maternal and fetal morbidity, often occurs during pregnancy. Diagnosis is often delayed due to overlapping symptoms and clinician reluctance, necessitating coordination between healthcare providers and community services.